2016
DOI: 10.1186/s12917-016-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling concentrations of antimicrobial drugs: comparative pharmacokinetics of cephalosporin antimicrobials and accuracy of allometric scaling in food-producing and companion animals

Abstract: BackgroundTo optimize antimicrobial dosing in different animal species, pharmacokinetic information is necessary. Due to the plethora of cephalosporin antimicrobials and animal species in which they are used, assessment of pharmacokinetics in all species is unfeasible. In this study we aimed to describe pharmacokinetic data of cephalosporins by reviewing the available literature for food producing and companion animal species. We assessed the accuracy of interspecies extrapolation using allometric scaling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The binding rate of CFQ to plasma proteins was found to be approximately 11% in buffalo calves (Venkatachalam & Dumka, 2015). Another study reported that the excretion extent of CFQ correlated with glomerular filtration rate in dogs; however, data in calves are not available (Taverne, van Geijlswijk, Heederik, Wagenaar, & Mouton, 2016). The rapid elimination of the drug in premature calves could be due to increased cardiac output, which would lead to an increase in glomerular filtration rate (Stritzke, Thomas, Amin, Fusch, & Lodha, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The binding rate of CFQ to plasma proteins was found to be approximately 11% in buffalo calves (Venkatachalam & Dumka, 2015). Another study reported that the excretion extent of CFQ correlated with glomerular filtration rate in dogs; however, data in calves are not available (Taverne, van Geijlswijk, Heederik, Wagenaar, & Mouton, 2016). The rapid elimination of the drug in premature calves could be due to increased cardiac output, which would lead to an increase in glomerular filtration rate (Stritzke, Thomas, Amin, Fusch, & Lodha, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to different endogenous factors, different causing agents and/ or pathogenetic factors or due to differences in antimicrobial treatment. Many antimicrobial agents are excreted through the kidney and thereby may lead to changes in the kidney (19,32). Additionally, Zwald et al (35) reported a higher use of antimicrobial treatment in conventionally dairy herds in comparison to organically herds.…”
Section: Discussionmentioning
confidence: 99%
“…Taverne FJ et al, 33 determined the pharmacokinetic data of cephalosporins by reviewing the available literature for food producing and companion animal species. They assessed the accuracy of allometric scaling in food-producing and companion animals.…”
Section: Methods Of Analysismentioning
confidence: 99%